Efektivitas Anestesi Umum Kombinasi Teknik Blok Skalp Menggunakan Levobupivakain 0,5 % terhadap Jumlah Fentanil Intraoperatif pada Pasien Kraniotomi Tumor Supratentorial di RSUP Dr. Sardjito - Hernandes, Crodia; Sudadi; Widyastuti, Yunita (Jurnal Komplikasi Anestesi, 2021)
Background: High dose opioid has been clinically proven to provide effective blockage of stimuli during head incision but it has several unwanted side effects. Scalp block is an alternative modality which has been used as an adjunct to general anesthesia aimed to blunt stress response throughout craniotomy while maintaining more stable condition in terms of less hemodynamic fuctuation. Objective: The study is aimed to compare fentanyl comsumption in general anesthesia combined with scalp block using saline and general anesthesia combined with scalp block using levobupivacaine 0.5% in patient which underwent craniotomy. Method: Twenty patients suffered from intracranial tumor with age ranging from 18 - 65 years who underwent craniotomy tumor removal at RSUP Dr. Sardjito were divided into 2 treatment groups in which the Levobupivacaine 0.5% block group received general anesthesia with a combination of scalp blocks using Levobupivacaine 0.5% while the control group received general anesthesia with a combination of scalp blocks using saline. Patients with local anesthetic allergy and uncontrolled bleeding were excluded from data collection. Result: The mean of fentanyl addition in patients with Levobupivacaine block was 513.0 mcg with a standard deviation of 164.2 mcg. Whereas in patients with Levobupivacaine block the average fentanyl addition was 1149.5 mcg with a standard deviation of 318.4 mcg. The mean difference in the addition of fentanyl between the two groups of 636.5 mcg showed a signifcant difference p = 0.001 (p <0.05). Conclusion: Combination of scalp blocks using Levobupivacaine 0,5% with general anesthesia showed reduction of fentanyl consumption alongside with statistically insignifcant hemodynamic fuctuation compared to general anesthesia and saline block in supratentorial brain tumor patient undergoing craniotomy. Hemodynamic profle in Levobupivacaine 0,5% group was maintained better than control group.